Cutaneous Adverse Drug Reactions (CADRs) at a Quaternary Care Hospital in South India: Focus on Reaction Time and Treatment Cost - Karunakaran, Priya; Kakkanatt, Anuradha; Bai, Jyothi (Indian Journal of Pharmacy Practice)
Background: Cutaneous Adverse Drug Reactions (CADRs) are a major problem in drug therapy and is one of the leading causes of morbidity and mortality in health care. The purpose of the study was to evaluate the Mean Reaction Time, Causality, Severity and Preventability of CADRs and Treatment cost associated with CADRs. Methods: A prospective, observational study of patients diagnosed with CADR was carried out over a period of one year in the Department of Dermatology and Department of Clinical Pharmacy at a quaternary care hospital in South India. Diagnosis of CADRs was confirmed by the dermatologist and Clinical Pharmacist evaluated the suspected CADRs for Causality by WHO-UMC and Naranjo’s scale, Severity by Hartwig and Siegel scale and Preventability by Schumock and Thornton criteria. Results: 42 CADRs were reported during the study period. Most commonly manifested CADR was Acneiform Eruption (23.8 %) followed by Maculopapular Rash (19.0%) and drugs used for the management of CADRs accounted for INR 5807.93. Most common offending drug group was Anti-infectives (33.3%) followed by Oral Steroids (23.8%). WHO and Naranjo scale rated 95.2% of CADR as probable and 4.7% as certain/ possible (Naranjo scale). Hartwig and Siegel scale marked 64.20% as moderate, 30.90% as mild and 4.70% as severe CADRs. According to Schumock and Thornton criteria 95.2% of CADR were not preventable and 4.7 % were definitely preventable. Conclusion: Awareness about CADRs is essential for early detection and prevention. The healthcare system should promote mandatory reporting of CADRs for ensuring safe drug use and patient care.
Keywords: Cutaneous Adverse Drug Reactions; Reaction Time; Causality; Severity; Preventability.